PENGARUH KESADARAN, KUALITAS PELAYANAN, SANKSI DAN PEMAHAMAN PERATURAN PERPAJAKAN PADA KEPATUHAN WAJIB PAJAK HOTEL - Kusuma, Ida Bagus Adinata; Supadmi, Ni Luh (E-Jurnal Akuntansi; Vol 17 No 1 (2016), 2016)
This research aims to determine the influence of the taxpayer awareness, quality of service, tax penalties and understanding of tax laws on taxpayer compliance. This research was conducted in Klungkung regency. The population in this study are all taxpayers effective hotel in the Department of Finance and Asset Management Revenue Klungkung regency. The number of samples in this study were 60 respondents, the sampling method used was accidental sampling. Collecting data using questionnaires. The data analysis technique used in this research is multiple linear regression. The results of this research showed that awareness of taxpayers, quality of service, tax penalties and understanding the tax laws and significant positive impact on taxpayer compliance in Klungkung regency.
Keywords: compliance; taxpayer awareness; quality of service; tax penalties; understanding tax regulations